Treatment Of Opioid Use Disorder Among Commercially Insured US Adults, 2008-17 - Shen, Karen; Barrette, Eric; Dafny, Leemore S (Health affairs (Millwood, Va.), 2020)
There is abundant literature on efforts to reduce opioid prescriptions and misuse, but comparatively little on the treatment provided to people with opioid use disorder (OUD). Using claims data representing 12-15 million nonelderly adults covered through commercial group insurance during the period 2008-17, we explored rates of OUD diagnoses, treatment patterns, and spending. We found three key patterns: The rate of diagnosed OUD nearly doubled during 2008-17, and the distribution has shifted toward older age groups; the likelihood that diagnosed patients will receive any treatment has declined, particularly among those ages forty-five and older, because of a reduction in the use of medication-assisted treatment (MAT) and despite clinical evidence demonstrating its efficacy; and treatment spending is lower for patients who choose MAT. These patterns suggest that policies supporting the use of MAT are critical to addressing the undertreatment of OUD among the commercially insured and that further research to assess the cost-effectiveness of treatment with versus without medication is needed.